HUBUNGAN ANTARA PERSEPSI TENTANG KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN PRODUKTIVITAS KERJA PADA PEKERJA BAGIAN PERAKITAN DI CV. MITRA DUNIA PALLETINDO TEMPEH-LUMAJANG - Endah Kurniawati. M.Psi, Siska Anggraini, S.Psi (El-QUDWAH, 2008)
In order productively work, countinously attention must be given to workers as a resources in the company in Safety given. The motivation in social economic as payment and social psyche as safety and protection working. Safety working is important to decrease working accident and working illness, whether Safety and Healthy Comitee should be used such as Minister of Labours regulation PER.05/MEN/1996. Besides, safety and healthy working are a necessary factor for productively working. Therefore, safety and healthy working must be understood by every workers. Based on many differences definition of workers, needs a further research. Therefore, the writer is inspired to research “The relationship between Safety and Healthy Working Perceptions and Working Productivity of Making-up Devision in CV. Mitra Dunia Palletindo Tempeh-Lumajang”. The objectives of the study are: (1) to know of Safety ang Healty working perception of making-up devision workers at CV. Mitra Dunia Palletindo, (2) to know the produvtivity of making-up devision workers at CV. Mitra Dunia Palletindo, and (3) to know the relationship between Safety ang Healty working perception and productivity of making-up devision workers at CV. Mitra Dunia Palletindo. This is comparative research with kuantitative approximation and correlation variety research. Samples were taking from 30 person. Data are taking by questionnaires method with Likert measuring method, data were completed by the result of interview, observation, and documentations. SPSS version 11.5 for windows are using to validity and reliable test. Based on a result of the research can knowing that Safety and Healthy Working of Workers perception in CV. Mitra Dunia Palletindo Tempeh-Lumajang, are five subject with high categories at 16,5% percentage, 20 subject with everage categories at 67 % percentage, and five subject with low categories at 16,5%. However in Working Productivity variable are six subject with high categories or 20% percentage and 24 subject with everage categories or 80% percentage. For knowing that Safety and Healthy Working Perception whether related to Productivity Working of Worker were used Spearman technical correlation analyze and SPSS version 11.5 for windows method. From correlation test can knowing positive coeffisien of correlation is 0, 730. therefore,   r calculation value r table are 0,730 0, 478. In this case can obtained if there are significant related between Safety and Health Working Perception and Productivity Working. Thus, the hipotesis: “There are positive related between Safety and Healthy Working Perception and Productivity Working” can accepted. It’s means, there are an increase of working productivity if Safety and Healthy Working Perception are increasing positively.Keyword: Perceptions, Safety and Healthy Working, Productivity.